Magical, mundane or marginal? : Deposition practices in the early neolithic Linearbandkeramik culture - Hofmann, Daniela (2020)
This volume takes its starting point from the increasingly frequent discovery of deliberately placed deposits on Early Neolithic Linearbandkeramik sites. This includes the placement of complete and still usable tools in the ground, as well as the creation of complex abandonment layers for example in wells or the destruction of immense material wealth in enclosure ditches.0This is the kind of behaviour that archaeologists generally interpret as ritual (often using the label "structured deposition"), but it is surprisingly little discussed for the Linearbandkeramik. This volume thus addresses two main goals. First, it contributes a new approach to the study of Linearbandkeramik world view by focusing on depositional practices more generally and addressing the connections between them. How do the more striking or unusual examples of deposition articulate with routine discard, and what does this tell us about how Linearbandkeramik societies saw these objects and their use? Second, given the wealth of data available for the Linearbandkeramik, there is an opportunity to contribute to the ongoing discussion regarding the variety of depositional phenomena across the European Neolithic and their theoretical and methodological implications.0This book thus combines chapters dealing with routine discard, as well as those concerned with burial evidence, formalised deposition of objects and feasting debris